Loss-of-function variant in chymotrypsin like elastase 3B (CELA3B) is associated with non-alcoholic chronic pancreatitis - Tóth, Andrea; Demcsák, Alexandra; Zankl, Florence; Oracz, Grzegorz; Unger, Lara Sophie; Bugert, Peter; Laumen, Helmut; Párniczky, Andrea; Hegyi, Péter; Rosendahl, Jonas; Gambin, Tomasz; Płoski, Rafał; et al. (Pancreatology, 2022)
Background - Genetic alterations in digestive enzymes have been associated with chronic pancreatitis (CP). Recently, chymotrypsin like elastase 3B (CELA3B) emerged as a novel risk gene. Thus, we evaluated CELA3B in two European cohorts with CP. - Methods - We analyzed all 8 CELA3B exons in 550 German non-alcoholic CP (NACP) patients and in 241 German controls by targeted DNA sequencing. In addition, we analyzed exons 6 and 7 by Sanger sequencing and the c.129+1G>A variant by melting curve analysis in 1078 further German controls. As replication cohort, we investigated up to 243 non-German European NACP patients and up to 1665 controls originating from Poland, Hungary, and Sweden. We assessed the cellular secretion and the elastase activity of recombinant CELA3B variants. - Results - In the German discovery cohort, we detected a splice-site variant in intron 2, c.129+1G>A, in 9/550 (1.64%) CP patients and in 5/1319 (0.38%) controls (P=0.007, OR=4.4, 95% CI=1.5-13.0). In the European replication cohort, this variant was also enriched in patients (9/178 [5.06%]) versus controls (13/1247 [1.04%]) (P=0.001, OR=5.1, 95% CI=2.1-12.0). We did not find the two previously reported codon 90 variants, p.R90C and p.R90L. - Conclusions - Our data indicate that CELA3B is a susceptibility gene for CP. In contrast to previous reports suggesting that increased CELA3B activity is associated with CP risk, the splice-site variant identified here is predicted to cause diminished CELA3B expression. How reduced CELA3B function predisposes to pancreatitis remains to be elucidated.
Online verfügbar: 23 June 2022, Artikelversion: 9 September 2022
Im Titel ist "(CELA3B)" kursiv geschrieben
Gesehen am 10.10.2023